"We Olaf": Pro[(x-)NP] constructions in Icelandic and beyond. Issue 1 (27th February 2020) - Sigurðsson, Halldór Ármann; Wood, Jim
Abstract : This article discusses and analyzes an unusual construction in Icelandic, with a plural pronoun in the singular reading and a directly juxtaposed or annexed NP (or DP), where, for example, við Ólafur (literally "we.NOM Olaf.NOM ") means 'Olaf and I'. We refer to this construction as Pro[NP]. Pro[NP] constructions have been reported for a handful of languages that lack a case system. Icelandic, in contrast, is a case language, and Pro[NP] in this language is case congruent : the pronoun and its NP/DP annex are always in the same case. No such language has to our knowledge ever been described in detail before; we provide the first in-depth investigation of case-congruent Pro[NP]. The article further compares the Icelandic construction to apparently similar constructions, including English we linguists and the Russian type of Pro[x-NP], as in my s Petej (literally "we.NOM with Peter.INSTR "), meaning 'Peter and I', showing that the Icelandic construction differs from these, despite having similar (but not identical) semantic properties. We propose that plural personal pronouns consist of two parts: a set of variables, {X, Y}, that determine the form of the pronoun, and an NP annex, which constrains the interpretation of the Y variable. Typically, the annex is phonetically silent (bare plural pronouns), but the Icelandic construction is unusual in that the annex is partly overt, thereby allowing a rare insight into the construction of plural personal pronouns.